Vertical shear capacity of steel-concrete composite deck slabs with steel ribs. (1st July 2022) - Xiang, Da; Liu, Yuqing; Shi, Yichi; Xu, Xiaoqing
Highlights: The theoretical calculation method of vertical shear capacity of the steel-concrete composite deck slab is proposed. The proposed method is validated via experiments and finite-element analysis and then simplified to be more engineer-friendly. The influential factors on vertical shear capacity are clarified. Abstract: The design of steel-concrete composite (SCC) deck slabs is likely governed by the vertical shear under small shear span-depth ratios. This paper aims to propose the calculation method of the vertical shear capacity of the SCC deck slab ( Vu ). Firstly, Vu is computed as the summation of the contributions of concrete layer ( Vc, u ) and steel members ( Vs, u ). Vc, u is treated as the product of the shear capacity of an equivalent reinforced concrete member without web reinforcement and a coefficient that reflects the effects of steel ribs. The formula of Vs, u is developed based on the force equilibrium conditions between the concrete layer and steel members and the section analysis considering the steel-concrete slips. Later, an iterative calculation method is proposed and verified against experiments and finite element (FE) models established via validated simulation techniques. Lastly, an extensive parametric analysis is implemented using the iterative method, from which a simplified calculation method was proposed and proved. Results indicate the iterative method is able to capture the effects of material and geometric parameters, shear span-effective depth ratio, and the degree of steel-concrete interaction. The increases in the heights of concrete layer and steel rib, as well as the rib thickness, can effectively enlarge Vu, while the influences of the steel plate's thickness and the steel-concrete slips are relatively minor. The iterative method produces accurate predictions with a mean error of 1% and a coefficient of variation of 0.05. The simplified method is more engineer-friendly and yields the average FE/test-predicted ratio being 1.11 as well as the percentage of safe predictions being 95%.